Photocatalytic decomposition of acetaldehyde gas on TiO2-SiO2 thin film photocatalyst ― a kinetic analysis - Abdul Aziz , Radhiyah; Sopyan, Iis (National Institute of Science Communication and Information Resources (CSIR), 2013)
TiO2-SiO2 thin film photocatalysts with 5 (TF95/5) and 10 w/w% (TF90/10) SiO2 contents have been prepared via sol-gel method. Characterization using X-ray diffractormeter and field emission scanning electron microscopy is performed to investigate the effect of SiO2 doping on the TiO2 thin film’s physico-chemical properties. The photocatalytic performance of the thin films is evaluated using the degradation of acetaldehyde gas at various initial concentrations under fixed intensity UV irradiation. A Langmuir-Hinshelwood kinetic model is used to analyze the kinetics of the photocatalytic reaction. It is found that the first order reaction rate constant (k) of the TF95/5 thin film photocatalyst (1.2438 µmol dm-3 min-1) is higher than that of TF90/10 thin film (0.3648 µmol dm-3 min-1). This is attributed to higher crystallinity of the TF95/5 thin film, resulting in more active charge carrier generation. However, TF90/10 thin film photocatalyst with smaller TiO2 particles shows four times stronger adsorbability of acetaldehyde than TF95/5 due to its higher surface area.